Spatial genetic heterogeneity in populations of a newly invasive whitefly in china revealed by a nation-wide field survey. - Dong Chu (PLoS ONE, 2013)
Even though introductions of exotic species provide ready-made experiments of rapid evolution, few studies have examined the genetic structure of an exotic species shortly after its initial introduction and subsequent spread. To determine the genetic structure of its populations during the initial introduction, we investigated the invasive sweet potato whitefly (Bemisia tabaci Q, commonly known as B. tabaci biotype Q) in China, which was introduced in approximately 2003. A total of 619 B. tabaci Q individuals in 20 provinces throughout China were collected and analyzed using five microsatellite loci.The introduced populations of B. tabaci Q in China represent eight genetic clusters with different geographic distributions. The populations in Yunnan Province, where B. tabaci Q was first detected, are genetically different from the other populations in China.The introduced populations of B. tabaci Q in China have high spatial genetic heterogeneity. Additional research is required to determine whether the heterogeneity results from multiple introductions, rapid evolution following one or few introductions, or some combination of multiple introductions and rapid evolution. The heterogeneity, however, is inconsistent with a single introduction at Yunnan Province, where B. tabaci Q was first detected, followed by spread.